Opportunities and Challenges in the Utilization of Warehouse Receipts for Coffee Farmers in Central Aceh District - Susiana Susiana; Khairani Khairani; Safrina Safrina; Lena Farsia (Universitas Syiah Kuala, 2021)
This article aims to analyze and explain the opportunities and challenges for coffee farmers in obtaining financing from banks using Warehouse Receipts (RG) as collateral. Capital for coffee production costs is one of the obstacles coffee farmers face in Central Aceh. As one of the Warehouse Receipt System (WRS) commodities, coffee can be used as collateral in the form of Warehouse Receipts issued by the WRS warehouse. It is under the provisions of Law No. 9 of 2009 concerning WRS. This research is empirical juridical research. Data were obtained through interviews with farmers/farmer groups, warehouse managers, and Disperindagkop Central Aceh District. This research found that Central Aceh farmers/farmer groups have an excellent opportunity to get financing with Warehouse Receipts as collateral. It can be seen from the support of the local Government in accelerating the certification process for 3 WRS warehouses during the COVID-19 pandemic. Currently, in Central Aceh, 5 WRS warehouses can accommodate the harvests of farmers/farmer groups. In addition, the existence of farmer groups and cooperatives can also strengthen farmers' opportunities to meet the require-ments for obtaining Warehouse Receipts. However, currently, the implementation of the WRS in Central Aceh is still not running optimally. It can be seen from the use of WRS, which is still very minimal. Of the five available WRS warehouses, only two have issued Warehouse Receipts, namely 110 SRG warehouses owned by the Government and PT. 3. In addition, currently, WRS is only used by entrepreneurs/cooperateves/ex-porters, while farmers/farmer groups have not yet utilized it. Until now, farmers/farmer groups still use the mechanism of selling coffee directly to collectors, which harms them in certain circumstances. The farmers do not use this WRS to obtain financing from the bank or delay selling. Another obstacle is related to the implementation of the Qanun on Sharia Financial Institutions in Aceh.